Hypoxia-induced RNASEH2A limits activation of cGAS-STING signaling in HCC and predicts poor prognosis. Issue 1 (February 2022) - Zhao, Fengbo; Liu, Aifen; Gong, Xiu; Chen, Hao; Wei, Jinhuan; Chen, Bin; Chen, Shiyin; Yang, Riyun; Fan, Yihui; Mao, Renfang
Background: Hypoxia is a hallmark of solid cancers, including hepatocellular carcinoma (HCC). There is scarce information about how hypoxia avoids immunologic stress and maintains a cancer-promoting microenvironment. Methods: The Cancer Genome Atlas, RNA-seq data, and Oncomine database were used to discover the correlation of RNASEH2A with tumor progression; then expression of RNASEH2A mRNA and protein were detected in HCC tissues and cells subjected to hypoxia or with the treatment of CoCl2 via real-time quantitative polymerase chain reaction and immunochemistry assays. Finally, the effect of RNASEH2A on cell proliferation and the involved signaling pathway was explored further. Results: RNASEH2A was positively correlated with tumor grade, size, vascular invasion, and poor prognosis. The expression of RNASEH2A mRNA and protein were increased and dependent on hypoxia-inducible factor 2α in HCC tissues and cell lines. Knockout of RNASEH2A in HCC cells greatly reduced cell proliferation and induced the transcription of multiple cGAS-STING (cyclic GMP–AMP synthase–stimulator of interferon genes) targeted type 1 interferon-related genes, including IFIT1, USP18, and CXCL10, which suggests knockout of RNASEH2A may produce immunologic stress and tumor suppressive effects. Conclusions: RNASEH2A plays a critical role and potentially predicts patient outcomes in HCC, which uncovers a new mechanism that RNASEH2A contributes to limit immunologic stress of cancer cells in the context of hypoxia.